2010
DOI: 10.1271/bbb.100405
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Both the N-Glycan-relevant and N-Glycan-irrelevant Structural Elements in the Recognition of Human Milk Lactoferrin by the 1CF11 Monoclonal Antibody

Abstract: Monoclonal antibody 1CF11 has been suggested to specifically recognize a certain carbohydrate epitope shared by glycoproteins in human external secretions. We examined the effect of cleaving the polypeptide backbone and removing N-linked oligosaccharides on the reactivity with 1CF11 of human milk lactoferrin (hLf) to elucidate the structural features of the 1CF11 epitope. We reveal by treating hLF with trypsin and/or N-glycosidase that both the N-glycan-relevant and N-glycan-irrelevant structural elements were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…[7][8][9] We have recently revealed that both hLf and its tryptic digests, after being deglycosylated with N-glycosidase F, showed a significant reduction in their immunoreactivity, although the reaction was never lost. 10) This result clearly indicated that hLf carried two distinct structural elements, the N-glycan-relevant and the N-glycanirrelevant portions, that were recognized by 1CF11 in the molecule. Elucidation of their precise chemical requirements may allow us to fully comprehend the significance of glycosylation in the protein.…”
mentioning
confidence: 81%
“…[7][8][9] We have recently revealed that both hLf and its tryptic digests, after being deglycosylated with N-glycosidase F, showed a significant reduction in their immunoreactivity, although the reaction was never lost. 10) This result clearly indicated that hLf carried two distinct structural elements, the N-glycan-relevant and the N-glycanirrelevant portions, that were recognized by 1CF11 in the molecule. Elucidation of their precise chemical requirements may allow us to fully comprehend the significance of glycosylation in the protein.…”
mentioning
confidence: 81%